Fibreoptic intubation under conscious sevoflurane sedation in anticipated difficult intubation cases with unfavorable conventional airway preparation - Karim, Habib Md Reazaul; Panda, Chinmaya Kumar; Arora, Prateek; Basumatary, Kartik (DiscoverSys Inc., 2019)
Airway management in maxillofacial and head and neck cancer patients has remained a challenge even after significant development towards difficult airway management. When such patients have multiple difficult intubation predictors, management becomes more thought-provoking. Mucosal preparation and sedation play a vital role in producing co-operative patient and successful procedure but is not always feasible. On the other hand, intravenous sedation lacks titratability and reversibility. We describe awake fiberoptic intubation in three adult patients having multiple difficult intubation predictors whose airway preparation was not feasible due to obscured surface anatomy and nil mouth opening. The cases were done under titrated conscious sevoflurane sedation of MACage 0.4-0.6 using nasopharyngeal airway and closed circuit. This report highlights that Sevoflurane based conscious sedation is a feasible alternative for awake fiberoptic intubation in patients whose airway anesthesia and blocks are not possible.